Adjuvanting Allergen Extracts for Sublingual Immunotherapy: Calcitriol Downregulates CXCL8 Production in Primary Sublingual Epithelial Cells - Pelst, Michael P.; Höbart, Clara; Wallaeys, Charlotte; De Rooster, Hilde; Gansemans, Yannick; Van Nieuwerburgh, Filip; Devriendt, Bert; Cox, Eric (Frontiers in Immunology, 2020)
Application of allergens onto the sublingual epithelium is used to desensitize allergic individuals, a treatment known as sublingual immunotherapy. However, the response of sublingual epithelial cells to house dust mite allergen and potential tolerance-promoting adjuvants such as Toll-like receptor ligands and calcitriol has not been investigated. In order to study this, primary sublingual epithelial cells were isolated from dogs and cultured in vitro. After 24h incubation with a Dermatophagoides farinae extract, a Dermatophagoides pteronyssinus extract, TLR2 ligands (FSL-1, heat-killed Listeria monocytogenes, Pam3CSK4), a TLR3 ligand (poly I:C), a TLR4 ligand (LPS) and calcitriol (1,25-dihydroxyvitamin D3), viability of the cells was analyzed using an MTT test and their secretion of IL-6, IL-10, CXCL8 and TGF-β1 was measured by ELISA. Additionally, to evaluate its potential effect as an adjuvant, sublingual epithelial cells were incubated with calcitriol in combination with a D. farinae extract followed by measurement of CXCL8 secretion. Furthermore, the effect of D. farinae and calcitriol on the transcriptome was assessed by RNA-sequencing. The viability of the sublingual epithelial cells was significantly decreased by poly I:C, but not by the other stimuli. CXCL8 secretion was significantly increased by D. farinae extract and all TLR ligands apart from LPS. Calcitriol significantly decreased CXCL8 secretion and co-administration with D. farinae extract reduced CXCL8 concentrations to levels seen in unstimulated sublingual epithelial cells. Although detectable, TGF-β1 secretion could not be modulated by any of the stimuli. IL-6 and IL-10 could not be detected at the protein nor at the mRNA level. It can be concluded that a D. farinae extract and TLR ligands augment the secretion of the pro-inflammatory chemokine CXCL8, which might interfere with sublingual desensitization. On the other hand, CXCL8 secretion was reduced by co-application of calcitriol and a D. farinae extract. Calcitriol therefore seems to be a suitable candidate to be used as adjuvant during sublingual immunotherapy.